Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

1) $\displaystyle \int_{-\pi}^\pi \frac{\sin^3(x)dx}{x^2}$

2) $\displaystyle \int_{0}^{\pi/2} \frac{\cos^3(x)\sin(x)dx}{1 + \cos^2x}$

I have no ideas how to deal with it. I tried to evaluate them by parts and use change of variables, but nothing works. Thanks in advance!

share|improve this question

3 Answers 3

up vote 1 down vote accepted

The second one may be done by substituting $u = \cos{x}$, $du = -\sin{x} dx$. You then get

$$\int_0^1 du \frac{u^3}{1+u^2}$$

You may substitute again by letting $v=u^2$, $dv = 2 u \, du$ and get

$$\int_0^1 dv \frac{v}{1+v} = \frac{1}{2}(1-\log{2})$$

share|improve this answer
    
Thanks a lot, you really helped me! –  Michael Feb 20 '13 at 19:25

For the 1st one , note that you're integrating an odd function over $[-\pi,\pi]$.

As David Mitra pointed out, the function is bounded($\lim_{x\to 0}\frac{\sin^3(x)}{x^2}=0$) , and continuous everywhere except 0 (and hence improperly integrable), allowing me to use the oddness of the function .

share|improve this answer
    
It should also be pointed out that the integrand is bounded (thus integrable). –  David Mitra Feb 20 '13 at 17:02
    
Ah, yes. I forgot to mention that. –  Ishan Banerjee Feb 20 '13 at 17:04
    
I do not think that noting that it is an odd function is quite enough, since we have a singularity at $x=0$. For instance you cannot argue in that manner for $\int_{-1}^1\frac{1}{x}=0$. You can argue that the Cauchy principle value is zero however. But David Mitra deals with this issue by realizing that the singularity is removable. –  Baby Dragon Feb 20 '13 at 17:13
    
Thank you very much for your help! –  Michael Feb 20 '13 at 19:25

There is a pretty way to solve the second integral. After substituting $t= \cos x$ denote

$$ I=\int_{0}^{1} \frac{t^3 dt}{1+t^2}\\ J=\int_{0}^{1}\frac{t dt}{1+t^2} = -\frac{\log 2}{2}\\ I+J=\int_{0}^{1}\frac{(t^3+t)dt}{1+t^2}=\int_{0}^{1}t dt= - \frac{1}{2} $$ Hence $I=\frac{\log 2-1}{2}$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.